Izoprostani in nevroprostani kot biološki označevalci oksidativnega stresa - Plesničar, Tjaša (Farmacevtski vestnik, 2019)
Oxidative stress is a state, when in favour of prooxidants, prooxidants and antioxidants become imbalanced. That happens when free radicals oxidize and destroy cell components. The main critical components being oxidized are lipids, from which isoprostanoids are released. Different series of isoprostanes are generated by free radical-induced peroxidation of arachidonic acid and series of neuroprostanes from docosahexaenoic acid located mainly in brain grey matter. Isoprostanes and neuroprostanes are considered biomarkers of oxidative stress in various diseases, such as central nervous system diseases, cancer, ishemia-reperfusion, genetic disorders, pre-clampsy, etc. That being said, isoprostanoids are not only produced by radical attacks, they are also biologically active compounds.
Keywords: biološki označevalci; izoprostani; nevroprostani; Oksidativni stres; preeklampsija